Predicting the Frequency of Pregnancy Induced Hypertension in Early Pregnancy by Maternal Serum Beta Human Chorionic Gonadotropin Levels - Fakhra Ashique, Ammara Nadeem, Nasreen Rehmatullah, Javaira Mumtaz, Anisa Saleem, Rizwana Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During early pregnancy raised beta human chorionic gonadotropin (β-HCG) level occurs during placental development. It may be used for identifying the pregnancy induced hypertension. There are certain factors that causes pregnancy induced hypertension and preeclampsia. However, many of the associated factors and specific cause is not known. Some common risk factors for preeclampsia are nulliparity, preeclampsia in a previous pregnancy, family history, history of hypertension, renal disease and antiphospholipid antibody syndrome or thrombophilia. However no single lab investigation can be done cost-effectively to make the early diagnosis of pregnancy induced hypertension. The objective of this study was to determine the frequency of Pregnancy induced hypertension in patients with high maternal serum β-HCG at early pregnancy ( 13-20 weeks of gestation). Methodology: A descriptive cross sectional study was conducted on Out Patient Department and in patient wards of the Obstetrics and Gynecology Department of KRL General Hospital, Islamabad. The study was done from 28th December 2018 to 27th June 2019. A total of 75 pregnant women, primary gravida and multi gravida with age range from18-40years with raised β-HCG at 13-20 weeks of gestation were included. All patients were observed during their stay in the hospital for the development of any complications of pregnancy induced hypertension. Results: Mean age of pregnant females was 32.12 ± 5.29 years. Mean gestational period was 17.31 ± 2.05 weeks. Mean β-HCG levels was 7.63±3.71. Pregnancy induced hypertension (PIH) in patients with high maternal serum β-HCG at 13-20 weeks of gestation was found in 64 (85.33%) patients, however there was no Pregnancy induced hypertension in 11 (14.65%) ladies. Conclusion: The outcome of this study concluded that frequency of pregnancy induced hypertension in pregnant femal with high maternal serum β-HCG at 13-20 weeks of gestation was high. Early screening of raised β-HCG can be made for the prevention of complications due to pregnancy induced hypertension. Keywords: Beta Human chorionic gonadotropin, pre-eclampsia, pregnancy induced hypertension.